Talent Allocation, Financial Intermediation and Growth: Evidence and Theory - Liliya Khabibulina; Andreas Hefti (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper we study the relationship between intersectoral wage inequality and economic growth. In the empirical part of the paper, we find a negative correlation of relative wages in the financial sector with respect to manufacturing sector with subsequent economic growth in case of the U.S. states from 1977 to 2011. We show that the result is robust to different standard estimation techniques and control variables. A similar while somewhat less robust result applies to the case of relative sector sizes as measured by the labor force. In the theoretical part we aim at constructing a tractable general equilibrium model of financial intermediation, entrepreneurship and growth with an imperfect labor market, that helps to explain the observed empirical regularities.
Keywords: J24; J31; O41; 330